Shariah Assessment Toward the Prosecution of Cybercrime in Indonesia - Abubakar, Achmad (2022)
This research aims to uncover how Islamic criminal acts towards social media crimes. This study also elaborates on how Islam assesses Indonesian criminal prosecution against social media crimes. The approach used is a juridical normative to assess the criminal law system in force in Indonesia with the Islamic criminal perspective as grand theory. The results found that crime through social media was adapted with the crime in Islamic law namely Hudūd, qisas diyat and tazir. This research also found that the Indonesian legal system provides legal rewards for perpetrators of crimes through social media charged with the Information and Electronic Transactions (ITE) Law still needs to be expanded. Crimes through social media most often threatened by the ITE Law are insults to the government or symbols of the state, threatening and defamation of others, insults to others and violating SARA (ethnicity, religion, race and intergroup). Cybercrimes related to adultery, alcoholism and terrorism must be considered because they are a serious threat. Prison penalties and fines that are most often sentenced to perpetrators of social media crimes include part of criminal tazir which is following Islamic criminal law